EVALUASI PENGGUNAAN ANTIBIOTIK PASIEN PNEUMONIA DENGAN METODE GYSSENS - Gemy Nastity Handayany; Dwi Yuliana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The purpose of this study is to determine the rationality of using antibiotics in pneumonia patients with the gyssens method in the inpatient installation of Nene Mallomo Hospital, Sidrap Regency for the 2021 period. This type of research is descriptive research with a quantitative approach conducted retrospectively. The results of the evaluation of the use of antibiotics based on the gyssens method were obtained the use of appropriate / rational antibiotics (category 0) by 14% and irrational use of antibiotics by 86% which were divided into other antibiotics that were more effective (category IVa) by 67%, the use of antibiotics too long (category IIIa) by 5%, the use of antibiotics too short (category IIIb) by 13% and the use of antibiotics not right dose (category IIa) by 1%. In this study, it can be concluded from the category assessed that the use of antibiotics in pneumonia patients at Nene Mallomo Hospital, Sidrap Regency is irrational.